Governance of Multipurpose Agricultural Cooperatives in North Gondar Zone, Ethiopia - Melak, Degsew; Derso, Beyene; Melesse, Birhanu (International Journal of Scientific Research and Management (IJSRM), 2018)
Although cooperatives play important role to sustainable development through the services they rendered to their members, governance of cooperatives becomes one of the biggest challenges to their sustainability. This study was conducted to examine the governance of multipurpose agricultural cooperatives using primary and secondary data sources. Primary data was collected using Household survey on 274 sample households. Focus group discussion and observation were used to supplement household survey data. Data was analyzed using descriptive statistics and multinomial logistic regression to identify key factors of cooperative governance. The finding of the study revealed that Consistent with focus group discussion results, 63.2%, 34% 56.7%, 45%, 57.7, 66.7%, 57.6% of cooperative members were not satisfied with the services of cooperatives in distribution of chemical fertilizer, improved seeds, credit service, market access service, supply of consumer goods, farm equipment, and profitability of cooperatives respectively. The majority of sample cooperatives examined in this study displays low degree of implementation of key cooperative governance principles. The econometric result revealed that rule of law of law, awareness, and trust were found to significantly influence the satisfaction of members in the performance of primary multipurpose agricultural cooperative. On the other hand, participation, transparency, and accountability were found to influence the dissatisfaction level of members to the performance of primary multipurpose agricultural cooperative. Recommendations include Improve knowledge gap of members, and Bye-law Enforcement.